The customer experience edge : technology and techniques for delivering an enduring, profitable and positive experience to your customers - Soudagar, Reza; Iyer, Vinay; Hildebrand, Volker (McGraw Hill-Ascent Audio, 2011)
"This excellent book makes it quite clear that your business has to focus on customer experience for 21st-century business success. It's more than refreshing to read the multiple case studies and well thought out approach and to hear the experienced voices of these authors. You've spent way too much time reading this endorsement. Read the book instead. It's so worth it." -Paul Greenberg, author of CRM at the Speed of Light "To differentiate yourself and delight your customers, you must manage your customers' experience with your goods or services, and your company. This invaluable book will show you why you must do this, and how to do it well." -Henry Chesbrough, author of Open Innovation and Professor at the Haas School of Business, University of California Berkeley "Technology advances are raising the human expectation of what an experience with a company can and should be. Finally, a book has been written that combines behavioral psychological, micro-economic, and technological considerations defining the customer experience edge." -Paul D'Alessandro, Partner, PricewaterhouseCoopers "As we move from Customer Experience 1.0 to Customer Experience 2.0, organizations and practitioners need a solid blueprint for success. Reza, Vinay, and Volker have created a clear and concise guide based on global best practices and proven principles. If you are ready to transform your organization, start by reading this book." -Lior Arussy, President, Strativity Group, and author of Customer Experience Strategy "The Customer Experience Edge is an excellent book to gain insights on how to leverage customer experience as a competitive advantage. The case studies serve as recipes that can be added to, modified, or simply baked into business plans to improve or deliver an exceptional customer experience." -Deb Dexter, Customer Service Director, Cardinal Health About the Book: Globalization and advanced technologies have given ever greater power to the person who decides if your business will succeed or fail-the customer. Whether your company serves consumers or other businesses, you can no longer compete on price and quality alone. To gain profits and market share, you have to deliver an experience that makes customers want to come back-and that sets you apart from the competition. You need to seize The Customer Experience Edge. Drawing on over sixty years of experience in shaping customer centric strategies and technologies for leading companies, three innovators bring you practical and proven ways to create your customer experience programs and overall business strategies. The key is to strike a balance between programs that are effective but prohibitively expensive and programs that fail to dedicate enough resources to be effective. In the middle ground lie the tools that everyone overlooks-foundational and disruptive technologies. These are the authors' main fields of expertise, and these are what make the customer experience profitable. The Customer Experience Edge explains how to combine strategy, leadership, organizational change, and technology to: Develop products and services that are highly valued by customers Form bonds that keep clients from turning to competitors Transform customers into your best advocates It's a new world of business, and customers are keenly aware that their loyalty is valuable currency. The Customer Experience Edge gives you a cost-effective, sustainable way to provide an unforgettable experience that builds loyalty and turns it into real, measurable profits.